Recovery of Silver as Silver Nitrate from Waste Silver Chloride in Quantitative Analysis Laboratory - Apisit Songsasen,; Niti Poowanathai, (Agriculture and Natural Resources, 2002)
Various methods for recovery of silver as silver nitrate from waste silver chloride in the quantitative analysis laboratory of the Department of Chemistry, Kasetsart University were investigated. Most of the methods based on the reduction of silver chloride to metallic silver and followed by the oxidation of metallic silver to silver nitrate by nitric acid. The electrolysis of silver (I) solution to give metallic silver also was investigated. The percent recovery and percent purity of the recovered-silver nitrate were in the range of 89.49-97.33 and 99.29-99.66, respectively. The reduction of silver chloride at 1,000 °C in electric furnace gave the highest percent recovery with high purity silver nitrate. The operation cost of each method was compared, and the reduction of silver chloride by formaldehyde, which gave 95.14% recovery and 99.29% purity, is recommended as a suitable method for recovery of silver as silver nitrate.